Development of LKPD Based on Scientific Approach on Matrix Materials in SMA - ADRIANI, NAZLI (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
The formulation of the problem from this research is Is the development of LKPD based on a scientific approach on matrix material in high school feasible to use? How are students' responses to LKPD based on a scientific approach to matrix material? as the purpose of this study is to determine whether the development of LKPD based on a scientific approach to matrix material in high school is feasible to use. To be able to find out how students respond to LKPD based on a scientific approach to matrix material. This research is a research and development Research and Development (R&D) that uses a 4D development model which consists of 4 stages, namely the definition stage, the design stage, the develop stage, and the dissemination stage. However, in this study, the researchers only limited it to the 3D stage, namely define, design and develop. The instrument in this study was a questionnaire sheet for the expert feasibility test. Based on the validation results from the validator, the LKPD assessment scores were obtained by two expert lecturers and one mathematics teacher with an average percentage value of 79% and categorized as